2021
DOI: 10.3389/fphar.2021.745061
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6: A Novel Target for Cardio-Cerebrovascular Diseases

Abstract: Cardio-Cerebrovascular Disease is a collective term for cardiovascular disease and cerebrovascular disease, being a serious threat to human health. A growing number of studies have proved that the content of inflammatory factors or mediators determines the stability of vascular plaque and the incidence of cardio-cerebrovascular event, and involves in the process of Cardio-Cerebrovascular Diseases. Interleukin-6 is a widely used cytokine that causes inflammation and oxidative stress, which would further result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 142 publications
2
58
0
1
Order By: Relevance
“…The dysregulation of IL-6 is closely related to the occurrence and outcome of many clinical diseases, including coronary heart disease, leukemia, hypertension, ischemic stroke and so on (45). Su et al demonstrated that elevated IL-6 induced by ischemia and hypoxia, oxidative stress, vascular occlusion and inflammation, partly leads to the production of the acute phase protein in the liver, thereby stimulating leukocyte recruitment and thrombosis, ultimately causing multiple cardiocerebrovascular diseases including ischemic stroke (46). Elevated serum IL-6 levels are implicated in a higher risk of incident stroke and mediate the racial disparity in stroke via inflammatory effects of risk factors (47).…”
Section: Dual Role Of Il-6 In Ischemic Strokementioning
confidence: 99%
“…The dysregulation of IL-6 is closely related to the occurrence and outcome of many clinical diseases, including coronary heart disease, leukemia, hypertension, ischemic stroke and so on (45). Su et al demonstrated that elevated IL-6 induced by ischemia and hypoxia, oxidative stress, vascular occlusion and inflammation, partly leads to the production of the acute phase protein in the liver, thereby stimulating leukocyte recruitment and thrombosis, ultimately causing multiple cardiocerebrovascular diseases including ischemic stroke (46). Elevated serum IL-6 levels are implicated in a higher risk of incident stroke and mediate the racial disparity in stroke via inflammatory effects of risk factors (47).…”
Section: Dual Role Of Il-6 In Ischemic Strokementioning
confidence: 99%
“…Drugs targeting inflammatory molecules have been clinically available for connective tissue diseases and other autoimmune diseases, and their application to cardiac diseases, including AF, is also underway ( Su et al, 2021 ). Anti-IL-6 receptor antibody (tocilizumab) is widely used for the treatment of RA.…”
Section: Anti-inflammatory Treatment and Afmentioning
confidence: 99%
“…Although extensive research studies have been conducted to improve the early diagnosis and treatment of CCVD, the survival rate of patients with CCVD remains surprisingly low [ 3 ]. Besides this, its features of high incidence, mortality, and disability pose huge burdens on the family and society [ 4 ]. Close association among cognitive impairment, CCVD, and mortality has been documented in a previous study [ 5 ], as well as the crucial role of aging in CCVD and neurodegenerative disorders [ 6 ].…”
Section: Introductionmentioning
confidence: 99%